Scientific papers and presentations - Davis, Martha (Academic Press, 2005)
Electronic publishing and electronic means of text and data presentation have changed enormously since the first edition was first published in 1997. This second edition applies traditional principles to today\'s, modern techniques. In addition to substantial changes on the poster presentations and visual aids chapters, the chapter on proposal writing discusses in more detail grant writing proposals. A new chapter has also been dedicated to international students studying in the United States. Selected Contents:-Searching and Reviewing Scientific Literature-The Graduate Thesis-Publishing in Scientific Journals-Reviewing and Revising-Titles and Abstracts-Ethical and Legal Issues-Scientific Presentations-Communication without words-The Oral Presentation-Poster Presentations
Effective communication skills in science
Keywords: knihovní věda; Library Science; knihovnictví, informační věda a muzeologie